PEMBUATAN LOAD BALANCER UNTUK SERVER MOODLE DI SEKOLAH VOKASI IPB UNIVERSITY - Aep Setiawan; Muhammad Raihan Aditia Suhendi; Erlin Arlitasari (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
SV IPB University has an LMS server to support online learning. The server contains an E-learning server application and a MOODLE database. When the MOODLE server serves many requests, it can cause the load received to be quite large. Server backup and load balanching are made to support server performance in serving clients. Server load balancer functions to distribute data traffic across two or more connection paths so that requests from clients can be routed evenly to each active server. The Load Balancing method used is Round Robin.Testing was carried out by clients by accessing the MOODLE LMS page through a load balancer server supported by two active MOODLE LMS servers. Based on the tests that have been done, the load balancer server successfully forwarded the request to the two MOODLE LMS servers, because when refreshed (F5) the website page displayed always alternates. It can be concluded that when the Web LMS is accessed, the load balancer successfully directs client requests to 2 MOODLE LMS servers in turn.